Model logitowy z klasami ukrytymi - Kapłon, Robert (Logit model with latent class analysis, 2005)
Using a single logit model for an entire population is potentially dangerous in masking the differentia effects due to consumer heterogeneity. Therefore, as a remedy a logit model are combined with a widely known statistical method as latent class analysis. Also, a more generic model based on finite mixture distribution is discussed. In particular author focusing on consumer decision strategy shows that logistic latent class analysis are a special case. The maximum likelihood function is optimized by means of an EM algorithm and Newton-Raphson in the M-step. The practical applicability of logit latent class analysis is demonstrated by real data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 326-335